2016
DOI: 10.1007/s12110-016-9260-0
|View full text |Cite
|
Sign up to set email alerts
|

Hunter-Gatherers and the Origins of Religion

Abstract: Recent studies of the evolution of religion have revealed the cognitive underpinnings of belief in supernatural agents, the role of ritual in promoting cooperation, and the contribution of morally punishing high gods to the growth and stabilization of human society. The universality of religion across human society points to a deep evolutionary past. However, specific traits of nascent religiosity, and the sequence in which they emerged, have remained unknown. Here we reconstruct the evolution of religious bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
103
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(111 citation statements)
references
References 101 publications
1
103
0
7
Order By: Relevance
“…Peoples et al find that among communities of hunter-gatherers the most popular kind of belief is animism. Then we find belief in an afterlife and shamanism [23]. We can suppose that these kinds of beliefs had and can have in the current societies psychological functions.…”
Section: Adaptability Of Religious Beliefsmentioning
confidence: 89%
See 1 more Smart Citation
“…Peoples et al find that among communities of hunter-gatherers the most popular kind of belief is animism. Then we find belief in an afterlife and shamanism [23]. We can suppose that these kinds of beliefs had and can have in the current societies psychological functions.…”
Section: Adaptability Of Religious Beliefsmentioning
confidence: 89%
“…In this sense perhaps it would be possible to explain at least some beliefs as a result of historic process of selection. We mean especially the oldest kind of beliefs like the concept of an afterlife or shamanism [23].…”
Section: The Fourth Meaning Of Naturalness Of Religious Beliefsmentioning
confidence: 99%
“…The label reflects the belief that all natural phenomena individually-e.g., each tree or river-possess a unique spirit or soul. Indeed, animism was probably the dominant mode of cognition among the social groups that started to coalesce approximately sixty thousand years ago (or possibly earlier) [48]. It is perhaps understandable that early societies concluded that natural phenomena possessed some sort of consciousness and soul, given that humans themselves were just starting to acquire cognisance of their own thoughts, feelings, and volition.…”
Section: Sacralitymentioning
confidence: 99%
“…In suggesting ways to control uncertainty by earning the favor or appeasing the hostility of unseen forces, they help ensure cooperation and group cohesion,131 even in hunter‐gatherer societies that recognize, in Gray's words, that ‘religious stories, while in some ways special and even sacred, are in the end just stories’ (p. 500) 52, 77. The cultural selection of religious stories with moralizing high gods, with their even stronger effects on cooperation, eventually allows the emergence or consolidation of large‐scale societies 128, 132, 133…”
Section: Evolving In the Religious And Scientific Nichesmentioning
confidence: 99%